Pendampingan Pastoral Bagi Keluarga Duka Pasien Covid 19 - Endang Damaris Koli; Anika Ch. Takene (Institut Agama Kristen Negeri Kupang, 2021)
The Covid-19 pandemic is a challenge for pastoral care. The characteristics of this pandemic form a method of prevention by limiting physical interaction. This changes various habits in people's lives, including when someone gets sick and dies, the services provided by the family and the hospital are not as usual. A patient who was infected with Covid-19 and then passed away brought great sorrow to his family. The family didn't have the chance to take care of him for the last time. This is a big trauma for the family. Our study aims to determine the trauma experienced by the family after the death of a family member. We are also trying to find a form of pastoral care that is able to restore the power of family life after the sad event. The method we use in this research is a qualitative approach. The research instrument used descriptive data (interviews), observation notes and literature studies. The results of our research include narratives of family grief, traumas and acts of pastoral care by the church. Our discussion refers to the detraumatization process as an effort to recover the family from grief.